Guidance for quality control practices and precision goals for CBCs based on IQMH patterns‐of‐practice survey. (23rd August 2018) - Johnston, Anna; Bourner, Gini; Martin, Tracy; McFarlane, Andrew; Good, David; Padmore, Ruth; Raby, Anne; Aslan, Berna
Abstract: Introduction: Effective medical laboratory quality management systems ensure confidence in analyzing and reporting accurate and reliable patient results. To guarantee quality assurance, each laboratory needs appropriate internal quality control (IQC) procedures to monitor their test systems. The Institute for Quality Management in Healthcare (IQMH) Centre for Proficiency Testing conducted a survey on quality control (QC) practices in routine hematology. Methods: An online survey was sent to 184 Ontario laboratories performing complete blood counts (CBC) and leukocyte differentials. Results: All participants used three levels of commercial QC for test system monitoring. Eighty percent of laboratories supplement with in‐house patient QC. The frequency of QC analysis was variable based on: Manufacturer recommendations (80%) Parameter stability (25%) Clinical impact of incorrect results (21%) Number of samples potentially requiring retesting if there is a QC failure (11%). All laboratories used established QC rules and limits to monitor results. They utilized various methods in establishing limits including: Standard deviation of QC results (60%) Manufacturer precision goals (55%) Published precision goals (24%) IQMH allowable performance limits (APLs) (37%). Conclusion: Considerable variation in QC practices of Ontario laboratories was identified, and consensus practice recommendations and precision goals were developed to guide and standardize QC practice.